Defending Traditions, Countering Intolerant Ideologies: Re-energizing the Role of Modin in Modern Java - Achmad Zainal Arifin (Al-Jami'ah Research Centre, 2017)
This paper discusses a neglected traditional Islamic figure called modin, who actually has potential and greater opportunity in countering the growing numbers of relatively new Islamic groups that perpetuate intolerant ideology. This paper is based on a fieldwork in the Village of Sidoluhur, Godean, Sleman, DIY. The primary data used for this research is derived from in-depth interviews with 17 people such as modin, village officers, mosques’ board members, and active jamaah (members) of the mosques. I argue that modin has a significant contribution in softening tensions among Muslims at a hamlet level. He will be functioning effectively in preserving local Islamic practices and, at the same time, filtering intolerant ideology in society. In so doing, contestations among modin, who might come from various Islamic groups, have to be carefully considered to maximize his roles in society, especially in countering intolerant views proposed by some transnational Islamic groups. [Artikel ini membahas peminggiran figur Islam tradisional di Jawa yang dikenal dengan sebutan modin. Figur ini sebenarnya mempunyai potensi dan peluang besar untuk menandingi perkembangan kelompok Islam yang menyebarkan ideologi intoleran. Artikel ini ditulis berdasarkan riset lapangan di Desa Sidoluhur, Godean, Yogyakarta, dengan melakukan wawancara mendalam terhadap tujuh belas informan meliputi modin, perangkat desa, pengurus masjid, dan jamaah masjid. Penelitian ini menunjukkan bahwa modin mempunyai kontribusi penting dalam meredam ketegangan umat di tingkat dusun. Ia berperan dalam melestarikan praktik Islam lokal sekaligus menyaring ideologi intoleran dalam masyarakat. Adanya kontestasi di antara modin yang berasal dari kelompok yang berbeda perlu menjadi pertimbangan untuk memaksimalkan peran modin di masyarakat dalam menandingi ideologi intoleran yang diusung oleh kelompok Islam transnasional.]